Application of Ecotourism Principles in The Development of Marine Tourism in Sanur - Sulaksana, I Gusti Bagus Gopala; Susianti, Hartanti Woro; Dianasari, Dewa Ayu Made Lily (Jurnal Penelitian Pariwisata, 2023)
The natural potential, strategic location and easy accessibility have made Sanur one of the most visited marine tourism areas. However, the development of marine tourism, in spite of having a positive impact, it also has negative ones, as it apparently harms the environment. This study aims to identify the extent to which ecotourism principles are applied in marine tourism product development efforts and programs in Sanur. This research is a descriptive qualitative research with the determination of informants through purposive sampling and snowball sampling techniques. Triangulation was also carried out as a test of data validity in this study. The results showed that overall the business and product development program of marine tourism in Sanur have implemented 5 principles of ecotourism according to Dowling. 3 principles that have been implemented well are Utilizing natural resources, Providing benefits to the community and Visitor satisfaction. However, the other 2 principles of ecotourism, namely nature-based and environmental education, still need to be improved in their application, in order to preserve nature which will ultimately establish sustainable tourism.